AgMeO composite Cu strip and application thereof in organic matter type thermal fuse

By using AgMeO complex Cu strips and using the extruded AgMeO/Cu/AgMeO structure, the problem of insufficient breaking and arc erosion resistance in organic temperature fuses in the prior art is solved, and low silver is achieved Content, high processing plasticity and uniform metallographic structure reduce production costs and quality abnormalities.

CN119305266APending Publication Date: 2025-01-14ZHEJIANG FUDA ALLOY MATERIALS TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411430956.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The electrical contact materials such as silver-copper alloys, silver copper oxide nickel oxide and other materials in existing organic temperature fuses have insufficient breaking ability and arc erosion resistance, and the preparation process leads to high silver content, high cost and uneven metallographic structure. .

Method used

AgMeO complex Cu strip is used to form a strip structure of AgMeO/Cu/AgMeO by extrusion, where the intermediate layer is Cu and the surface layer is AgMeO. The overall structure is obtained by high-temperature sintering and annealing rolling, which reduces the amount of silver used and 提高了金相组织的均匀性。

Benefits of technology

The silver content is reduced, the processing plasticity and metallographic structure uniformity is improved, the material cost is reduced, and the bubbles and hole problems are avoided, which enhances the electrical performance and production stability of the strip.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119305266A_ABST
    Figure CN119305266A_ABST
Patent Text Reader

Abstract

The invention provides an AgMeO composite Cu strip and application thereof in an organic matter type thermal fuse, the AgMeO composite Cu strip is a strip which is formed by extruding an AgMeO composite Cu spindle and has an overall structure of AgMeO / Cu / AgMeO, the AgMeO composite Cu strip comprises a middle layer and a surface layer arranged on the surface of the middle layer, the surface layer is made of AgMeO, the middle layer is made of Cu, and Me comprises Cu. The strip with the Cu layer in the middle is adopted to replace an AgMe or AgMeO strip, the proportion of the Cu in the middle can reach 50%-90%, and the minimum thickness of the upper AgMeO layer and the lower AgMeO layer can reach 0.005 mm, so that the overall silver content of the strip can be reduced to about 11%, the usage amount of precious metal is greatly reduced, and the material cost is reduced; and meanwhile, an Ag layer is not needed in the middle, the bonding strength of the AgMeO layer and the Cu layer can be guaranteed by directly adopting an extrusion silver compounding mode, and the use of precious metal is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of temperature fuses, and in particular to an AgMeO-Cu composite strip and application thereof in an organic temperature fuse. Background Art

[0002] Thermal fuses, also called thermal fuses, are temperature sensing circuit cut-off devices. Thermal fuses can sense overheating caused by abnormal operation of electrical and electronic products, thereby cutting off the circuit to avoid fire. The structure of organic fuses (OTCO) includes a metal shell, a spring, a movable electrode and a temperature sensor. The principle is that when the temperature reaches the melting temperature, the temperature sensor melts, and the movable electrode is separated from the contact line under the action of the straight spring, thereby disconnecting the circuit. It is commonly used in rice cookers, bread machines, washing machines, refrigerators, hair dryers, electric irons, printers, heated seats, etc.

[0003] At present, the commonly used electrical contact materials for the movable electrode in the organic type temperature fuse are silver-copper alloy, silver-copper-oxide-nickel oxide, silver-copper-oxide-nickel oxide / silver-copper alloy / silver-copper-oxide-nickel oxide, etc. Silver-copper alloy material has good plasticity and a softening temperature of 200-350°C, but its breaking ability and arc erosion resistance are poor; silver-copper-oxide-nickel oxide material has average plasticity, average breaking and arc erosion resistance, but its softening temperature is relatively high, at 500-600°C; silver-copper-oxide-nickel oxide / silver-copper alloy / silver-copper-oxide-nickel oxide has excellent plasticity, excellent breaking and arc erosion resistance, but its preparation adopts an internal oxidation process, which makes the thickness of the silver-copper-oxide-nickel oxide layer unstable and the metallographic uniformity of the oxide layer is poor.

[0004] After searching, patent CN 115527817 A prepares silver metal oxide / silver metal alloy / silver metal oxide strip by internal oxidation process, vacuum smelting silver and metal into alloy ingots, then planing to remove oxide scale, rolling it into silver metal alloy strip, and performing internal oxidation operation, so that the two sides of the silver metal alloy strip are internally oxidized to form a silver metal oxide surface layer, forming a silver metal oxide / silver metal alloy / silver metal oxide composite structure. However, the thickness of the silver metal oxide layer of the product made by the internal oxidation process of the strip in this patent is unstable, the metallographic structure is uneven, and the overall silver content of the strip reaches more than 85%, which is high in silver content, resulting in high production and processing costs.

[0005] Therefore, it is urgent to develop an electrical contact material for an organic thermal fuse that not only meets the requirements of low silver content, but also has excellent processing plasticity and uniform metallographic structure. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide an AgMeO-Cu composite strip and its application in an organic type temperature fuse.

[0007] The technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention provides an AgMeO-composite Cu strip, which is a strip having an overall structure of AgMeO / Cu / AgMeO formed by extruding an AgMeO-composite Cu ingot, comprising an intermediate layer and a surface layer arranged on the surface of the intermediate layer, wherein the surface layer is made of AgMeO, the intermediate layer is made of Cu, and the intermediate layer accounts for 50%-90% of the overall thickness of the strip.

[0009] Preferably, the AgMeO-Cu ingot comprises an AgMeO sleeve and a Cu rod therein, and the AgMeO sleeve is obtained by pressing and extruding AgMeO powder into an AgMeO ingot and then sintering and extruding.

[0010] Preferably, the preparation method comprises the following steps:

[0011] S1. Mix Ag and Me in proportion;

[0012] S2, melting and atomizing the ingredients to form AgMe powder, drying the AgMe powder and performing screening treatment;

[0013] S3, oxidizing the sieved AgMe powder to obtain AgMeO powder, crushing, refining and sorting;

[0014] S4, preparing an AgMeO ingot by isostatic pressing the AgMeO powder processed in step S3;

[0015] S5, sintering the AgMeO ingot at high temperature and extruding it into an AgMeO sleeve;

[0016] S6, pressing a Cu rod into the middle of the AgMeO tube sleeve to make an AgMeO-Cu ingot;

[0017] S7, heating and extruding the AgMeO-Cu composite ingot, and then annealing and rolling it into an AgMeO-Cu composite strip.

[0018] Preferably, in step S1, Me includes Cu, wherein the proportion of Ag is 80-90% and the proportion of Cu is 10-20%.

[0019] Preferably, in step S1, Me includes Cu and Ni, wherein the proportion of Ag is 90-96%, the proportion of Cu is 3-5%, and the proportion of Ni is 0.1-0.5%.

[0020] Preferably, in step S2, the smelting temperature is 1000-1300°C, the refining time is 5-8 min, the water pressure of the high-pressure water atomization spray plate is 100-200 MPa, and the screen is 100-150 mesh.

[0021] Preferably, in step S3, the oxidation temperature is 500-750°C, the oxidation pressure is 0.4-1MPa, and the oxidation time is 5-10h; the crushing speed is 1000-2000r / min, the crushing time is 5-15min, and argon protection is used during the crushing process; and the ultrafine sorting machine is used for sorting, and the sorting particle size is 3-10um;

[0022] In step S4, the isostatic pressing pressure is 130-170 MPa, and the pressure is maintained for 30-60 seconds.

[0023] Preferably, in step S5, the sintering temperature of the AgMeO ingot is 800-900°C, the sintering time is 2-5h, the outer diameter of the extruded tube is 60-90mm, and the wall thickness is 5-20mm.

[0024] Preferably, in step S7, the heating temperature is 800-900°C, the AgMeO-Cu ingot is extruded to a thickness of 4-6 mm and a width of 50-80 mm; the annealing temperature is 350-450°C, the holding time is 90-120 min, the rolling deformation is 10%-80%, and the strip thickness is 0.06-0.15 mm.

[0025] The second aspect of the present invention is to provide a use of the AgMeO-Cu composite strip as described above as an electrical contact material of a movable electrode in an organic thermal fuse.

[0026] The beneficial effects of the present invention are as follows:

[0027] 1. A strip with a Cu layer in the middle is used to replace the AgMe or AgMeO strip. The proportion of the middle Cu can reach 50%-90%, and the upper and lower AgMeO layers can be as small as 0.005mm, so that the overall silver content of the strip can be reduced to about 11%, the use of precious metals is greatly reduced, and the material cost is reduced; in the existing AgMeO Cu-compounding process, there is an Ag layer of about 10% between AgMeO and Cu, which is used to improve the bonding strength of AgMeO and Cu. The present invention prepares the AgMeO Cu-compounding strip. During the preparation process, no Ag layer is required in the middle. The bonding strength of the AgMeO layer and the Cu layer can be ensured by directly extruding the silver-compounding method, further reducing the use of precious metals; in one embodiment of the present invention, the AgMeO Cu-compounding strip is used to replace the AgMeO strip. The maximum proportion of the middle Cu reaches 90%, and the Cu layer has good processing performance, so that the processing plasticity of the strip prepared by the present invention is better than that of the AgMeO strip, and the minimum can be processed to 0.06mm, and it can be mass-produced.

[0028] 2. The existing AgMeO strip preparation adopts a strip oxidation process, in which AgMe is melted and rolled into a strip, and then the strip is oxidized to make an AgMeO strip. The strip produced by this process is prone to shrinkage during the casting process, and the inside of the plate is not dense, resulting in blistering and holes in the strip, making the yield rate extremely low. The AgMeO composite Cu strip made by powder oxidation has a large extrusion ratio, a dense internal structure, and a stable AgMeO layer thickness, which can well solve the problem of blistering and holes. In addition, the use of a high-energy crusher and an ultra-fine separator makes the metallographic structure of the oxidized powder more uniform, and there will be no oxygen-rich and oxygen-poor areas, and the electrical properties of the strip are more stable.

[0029] 3. When making pipe sleeves from existing extruded composite strips, the pipes are rolled by a plate coiling machine, and then the joints are welded. During the heating and extrusion composite process, the pipe sleeves are prone to rupture, resulting in damage to the composite surface and inclusions at the joints. However, the use of extruded seamless pipe sleeves can avoid inclusions and pipe sleeve rupture during the extrusion composite process, improve the stability of the extrusion composite, and reduce quality abnormalities. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0031] Figure 1 It is a schematic diagram of the cross-sectional structure of the material of the present invention;

[0032] Figure 2 The process flow chart of the material preparation method of the present invention;

[0033] Figure 3 It is a schematic structural diagram of the AgMeO-Cu ingot of the present invention;

[0034] Figure 4 It is a schematic structural diagram of the AgMeO-Cu extruded composite strip of the present invention;

[0035] Figure 5 This is a schematic diagram of the metallographic structure of AgMeO composite Cu of the present invention. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0037] Example 1

[0038] A method for preparing a AgCuO-coated Cu strip for an organic thermal fuse comprises the following steps:

[0039] a. Weigh 2.47kg Cu ​​and 17.53kg silver according to the proportion;

[0040] b. Add Ag and Cu into a medium frequency induction furnace, smelting temperature: 1200℃, refining time: 6min, high pressure water atomization spray plate water pressure 100MPa, atomize into AgCu powder, then dry the AgCu powder and sieve with a 150 mesh screen;

[0041] c. Put the sieved AgCu powder into an internal oxidation furnace at an oxidation temperature of 550°C, an oxygen pressure of 0.6MPa, and an oxidation time of 6h to make AgCuO powder. The AgCuO powder is crushed with high energy at a speed of 1000r / min and a crushing time of 12min under argon protection. The crushed AgCuO powder is added to an ultrafine classifier at a pressure of 0.6MPa and a classifying wheel speed of 100Hz, with an average particle size of 3-10um.

[0042] d. Load the AgCuO powder into an isostatic pressing device, set the isostatic pressing pressure to 170 MPa, and maintain the pressure for 50 seconds to make an AgCuO ingot;

[0043] e. Put the AgCuO ingot into the sintering furnace. The sintering furnace equipment parameters are as follows: sintering temperature: 850°C, sintering time: 4h, and extruded into a tube sleeve with an outer diameter of 80mm and a wall thickness of 10mm;

[0044] f. Grind the inner wall of the AgCuO tube sleeve and the outer wall of the Cu rod clean, and press the Cu rod into the AgCuO tube sleeve;

[0045] g. The AgCuO-Cu ingot prepared in f is heated to 880°C and extruded into a composite blank with a thickness of 5 mm and a width of 80 mm;

[0046] h. Anneal the blank at 380℃ in a box for 120min, control the deformation at 40% in each pass, and after multiple annealing and rolling, the strip can be rolled to a finished product of 0.09mm;

[0047] The overall silver content of the AgCuO-Cu composite strip prepared in this embodiment can be reduced by 45-50%.

[0048] Example 2

[0049] A method for preparing a AgCuONiO composite Cu strip for an organic thermal fuse comprises the following steps:

[0050] a. Weigh Cu: 0.81kg, Ni: 0.06kg, Ag: 19.13kg according to the proportion of ingredients;

[0051] b. Add Ag, Cu and Ni into a medium frequency induction furnace, smelting temperature: 1250℃, refining time: 7min, high pressure water atomization spray plate water pressure 120MPa, atomize into AgCuNi powder, then dry the AgCuNi powder and sieve it with a 150 mesh screen;

[0052] c. Put the sieved AgCuNi powder into an internal oxidation furnace at an oxidation temperature of 600°C, an oxygen pressure of 0.6MPa, and an oxidation time of 5h to prepare AgCuONiO powder. The AgCuONiO powder is crushed with high energy at a speed of 1500r / min and a crushing time of 8min under argon protection. The crushed AgCuONiO powder is added to an ultrafine classifier at a pressure of 0.7MPa and a classifying wheel speed of 80Hz, with an average particle size of 3-10um.

[0053] d. Load the AgCuONiO powder into an isostatic pressing device, set the isostatic pressing pressure to 150 MPa, and maintain the pressure for 60 seconds to make an AgCuONiO ingot;

[0054] e. Put the AgCuONiO ingot into the sintering furnace. The sintering furnace equipment parameters are as follows: sintering temperature: 850°C, sintering time: 4h, and extruded into a tube sleeve with an outer diameter of 80mm and a wall thickness of 8mm;

[0055] f. Grind the inner wall of the AgCuONiO tube sleeve and the outer wall of the Cu rod clean, and press the Cu rod into the AgCuONiO tube sleeve;

[0056] g. The AgCuONiO composite Cu ingot prepared in f was heated to 880°C and extruded into a composite blank with a thickness of 5 mm and a width of 60 mm;

[0057] h. Anneal the blank at 380℃ in a box for 120min, control the deformation at 60% in each pass, and after multiple annealing and rolling, the strip can be rolled to a finished product of 0.085mm;

[0058] The overall silver content of the AgCuONiO composite Cu strip prepared in this embodiment can be reduced by 40-45%.

[0059] Example 3

[0060] A method for preparing a AgCuO-coated Cu strip for an organic thermal fuse comprises the following steps:

[0061] a. Weigh Cu: 1.97kg, Ag: 18.03kg according to the proportion of ingredients;

[0062] b. Add Ag and Cu into a medium frequency induction furnace, smelting temperature: 1200℃, refining time: 5min, high pressure water atomization spray plate water pressure 100MPa, atomize into AgCu powder, then dry the AgCu powder and sieve it with a 100 mesh screen;

[0063] c. Put the sieved AgCu powder into an internal oxidation furnace at an oxidation temperature of 550°C, an oxygen pressure of 0.6MPa, and an oxidation time of 6h to make AgCuO powder. The AgCuO powder is crushed with high energy at a speed of 1000r / min and a crushing time of 7min under argon protection. The crushed AgCuO powder is added to an ultrafine classifier at a pressure of 0.8MPa, a classifying wheel speed of 120Hz, and an average particle size of 3-10um.

[0064] d. Load the AgCuO powder into an isostatic pressing device, set the isostatic pressing pressure to 150 MPa, and maintain the pressure for 60 seconds to make an AgCuO ingot;

[0065] e. Put the AgCuO ingot into a sintering furnace. The sintering furnace equipment parameters are as follows: sintering temperature: 850°C, sintering time: 4h, and extruded into a tube sleeve with an outer diameter of 60mm and a wall thickness of 7mm;

[0066] f. Grind the inner wall of the AgCuO tube sleeve and the outer wall of the Cu rod clean, and press the Cu rod into the AgCuO tube sleeve;

[0067] g. The AgCuO-Cu ingot prepared in step f was heated to 880°C and extruded into a composite blank with a thickness of 4 mm and a width of 50 mm;

[0068] h. Anneal the blank at 380℃ in a box for 120min, control the deformation at 40% in each pass, and after multiple annealing and rolling, the strip can be rolled to a finished product of 0.06mm;

[0069] The overall silver content of the AgCuO-Cu composite strip prepared in this embodiment can be reduced by 45-50%.

[0070] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. An AgMeO-Cu composite strip, characterized in that: The strip has an overall structure of AgMeO / Cu / AgMeO formed by extruding AgMeO-Cu ingots, and includes an intermediate layer and a surface layer arranged on the surface of the intermediate layer. The surface layer is made of AgMeO, and the intermediate layer accounts for 50%-90% of the overall thickness of the strip.

2. The AgMeO-Cu composite strip according to claim 1, characterized in that: The AgMeO-Cu ingot comprises an AgMeO sleeve and a Cu rod therein, and the AgMeO sleeve is obtained by pressing and extruding AgMeO powder into an AgMeO ingot and then sintering and extruding.

3. The AgMeO-Cu composite strip according to claim 1, characterized in that: The preparation method thereof comprises the following steps: S1. Mix Ag and Me in proportion; S2, melting and atomizing the ingredients to form AgMe powder, drying the AgMe powder and performing screening treatment; S3, oxidizing the sieved AgMe powder to obtain AgMeO powder, crushing, refining and sorting; S4, preparing an AgMeO ingot by isostatic pressing the AgMeO powder processed in step S3; S5, sintering the AgMeO ingot at high temperature and extruding it into an AgMeO sleeve; S6, pressing a Cu rod into the middle of the AgMeO tube sleeve to make an AgMeO-Cu ingot; S7, heating and extruding the AgMeO-Cu composite ingot, and then annealing and rolling it into an AgMeO-Cu composite strip.

4. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S1, Me includes Cu, wherein the proportion of Ag is 80-90% and the proportion of Cu is 10-20%.

5. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S1, Me includes Cu and Ni, wherein, The proportion of Ag is 90-96%, the proportion of Cu is 3-5%, and the proportion of Ni is 0.1-0.5%.

6. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S2, the smelting temperature is 1000-1300°C, the refining time is 5-8min, the water pressure of the high-pressure water atomization spray plate is 100-200MPa, and the screen is 100-150 mesh.

7. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S3, the oxidation temperature is 500-750°C, the oxidation pressure is 0.4-1MPa, and the oxidation time is 5-10h; the crushing speed is 1000-2000r / min, the crushing time is 5-15min, and argon protection is used during the crushing process; the ultra-fine sorting machine is used for sorting, and the sorting particle size is 3-10um; In step S4, the isostatic pressing pressure is 130-170 MPa, and the pressure is maintained for 30-60 seconds.

8. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S5, the sintering temperature of the AgMeO ingot is 800-900°C, the sintering time is 2-5h, the outer diameter of the extruded tube is 60-90mm, and the wall thickness is 5-20mm.

9. The AgMeO-Cu composite strip according to claim 3, characterized in that: In step S7, the heating temperature is 800-900°C, and the AgMeO-Cu ingot is extruded to a thickness of 4-6 mm and a width of 50-80 mm; the annealing temperature is 350-450°C, the holding time is 90-120 min, the rolling deformation is 10%-80%, and the strip thickness is 0.06-0.15 mm.

10. Use of the AgMeO-Cu composite strip as claimed in any one of claims 1 to 9 as an electrical contact material for a movable electrode in an organic thermal fuse.

Citation Information

Patent Citations

  • Silver metal oxide electric contact material, preparation method thereof and application of silver metal oxide electric contact material in organic matter type thermal fuse

    CN115527817A

  • Temperature fuse and sliding electrode used in temperature fuse

    CN103946946A

  • Electrode material for thermal-fuse movable electrode

    CN104272419A

  • Preparing method of silver tin oxide copper clad strip

    CN108043894A

  • Silver-copper melt with sandwich structure

    CN109585235A